Characterization of Partial Gene Deletions in Type III von Willebrand Disease with Alloantibody Inhibitors - Mancuso, David J; Tuley, Elodee A; Castillo, Ricardo; de Bosch, Norma; Mannucci, Pler M; Evan Sadler, J (Thrombosis and Haemostasis, 1994)
von Willebrand factor gene deletions were characterized in four patients with severe type III von Willebrand disease and alloantibodies to von Willebrand factor. A PCR-based strategy was used to characterize the boundaries of the deletions. Identical 30 kb von Willebrand factor gene deletions which include exons 33 through 38 were identified in two siblings of one family by this method. A small 5 base pair insertion (CCTGG) was sequenced at the deletion breakpoint. PCR analysis was used to detect the deletion in three generations of the family, including two family members who are heterozygous for the deletion. In a second family, two type III vWD patients, who are distant cousins, share an -56 kb deletion of exons 22 through 43. The identification and characterization of large vWF gene deletions in these type III vWD patients provides further support for the association between large deletions in both von Willebrand factor alleles and the development of inhibitory alloantibodies.